Assessment of challenges in patrol vehicles and with equipment among law enforcement officers. (April 2023) - Hsiao, Hongwei
Abstract: Understanding the challenges Law Enforcement Officers (LEOs) have encountered with their vehicle and equipment and the correlation between equipment configuration and LEO body dimensions is critical for improving vehicle/equipment specifications to better accommodate today's LEOs. 974 LEOs participated in a study on their vehicle, equipment, and body measurements at 12 sites across the U.S. 88% participants reported discomfort/pain at the end of a shift. The most affected body areas were the lower back and hips. Handguns, radios, and handcuffs on duty belt and seat adjustment were associated with the discomfort/pain. 41% LEOs identified inadequate seat adjustment. Stature, buttock-popliteal length, eye height (sitting), knee height (sitting), shoulder-grip length, popliteal height, sitting height, hip breadth, and body weight were key parameters associated with seat adjustment needs. A third of officers experienced neck pain associated with the use of in-vehicle mobile data terminals and more fore/aft adjustment was needed. Highlights: Improved vehicle equipment layout and seat adjustment are in need for officers. Female officers need more up/down and males need more fore/aft seat adjustments. 88% officers reported some pain at the end of a shift mostly at lower back and hip. Handguns, radios, and handcuffs on duty belts are sources with seated discomfort. Seat adjustment needs are associated with popliteal height and other 8 dimensions.